Olga Tokarczuk’s Game with the Rules of Criminal Novels: The Case of “Plough Through the Bones of the Dead” - Wzorek, Anna (Respectus Philologicus, 2013)
This article presents the game Olga Tokarczuk plays with criminal narration as based on her novel, Plough Through the Bones of the Dead (2009). The main problem is that this famous writer, recipient of numerous prestigious awards, here disregards a series of “iron” rules that have guided detective novels for ages to write a pastiche of a criminal novel. The analysis reveals that Tokarczuk retreats from common frameworks of criminal novels, only making a delicate reference to the problem of an “island.” The writer also discards the rule that a murder has to be the starting point for the criminal plot. She not only delays the moment of introduction of the criminal motive, but also, contrary to the abovementioned “iron” rules, avoids presenting the prerequisites necessary to unmask the criminal. She is far more interested in the daily life of the protagonist/narrator than in the circumstances surrounding the four murders. In the world created by Tokarczuk, there is no detective who conducts an investigation. At the end of this quasi-criminal novel, the very perpetrator discloses the secret of the mysterious deaths. Tokarczuk’s rather free attitude toward the rules of the criminal novel is also manifested in her choice to leave the murderer unpunished. Moreover, the author introduces an improbable method of crime. In Plough Through the Bones of the Dead—a title which also provides proof that this is a pastiche of a criminal novel—one will not find any references to classical criminal novels, but quotations from William Blake’s mystic poetry.
Keywords: Contemporary Literature; Criminal Novel; Olga Tokarczuk; Pastiche; Popular Novel